Identifying novel Plasmodium falciparum erythrocyte invasion receptors using systematic extracellular protein interaction screens. (13th May 2013) - Bartholdson, S. Josefin; Crosnier, Cécile; Bustamante, Leyla Y.; Rayner, Julian C.; Wright, Gavin J.
Summary: The invasion of host erythrocytes by the parasite Plasmodium falciparum initiates the blood stage of infection responsible for the symptoms of malaria. Invasion involves extracellular protein interactions between host erythrocyte receptors and ligands on the merozoite, the invasive form of the parasite. Despite significant research effort, many merozoite surface ligands have no known erythrocyte binding partner, most likely due to the intractable biochemical nature of membrane‐tethered receptor proteins and their interactions. The few receptor–ligand pairs that have been described have largely relied on sourcing erythrocytes from patients with rare blood groups, a serendipitous approach that is unsatisfactory for systematically identifying novel receptors. We have recently developed a scalable assay called AVEXIS (for AVidity‐based EXtracellular Interaction Screen), designed to circumvent the technical difficulties associated with the identification of extracellular protein interactions, and applied it to identify erythrocyte receptors for orphan P. falciparum merozoite ligands. Using this approach, we have recently identified Basigin (CD147) and Semaphorin‐7A (CD108) as receptors for RH5 and MTRAP respectively. In this essay, we review techniques used to identify Plasmodium receptors and discuss how they could beapplied in the future to identify novel receptors both for Plasmodium parasites but also other pathogens.